Low-intensity laser phototherapy enhances the proliferation of dental pulp stem cells under nutritional deficiency - Cacio MOURA NETTO; Leila Soares FERREIRA; Carlos Magno MARANDUBA; Anna Carolina Volpi MELLO-MOURA; Marcia Martins MARQUES (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract Dental trauma in immature permanent teeth can damage pulp vascularization, which leads to necrosis and cessation of apexogenesis. Studies on tissue engineering using stem cells from human exfoliated deciduous teeth (SHEDs) have yielded promising results. Laser phototherapy (LPT) is able to influence the proliferation and differentiation of these cells, which could improve tissue engineering. SHEDs (eighth passage) were seeded into 96-well culture plates (103 cells/well) and were grown in culture medium supplemented with 15% defined fetal bovine serum (FBS) for 12 h. After determining the appropriate nutrition deficiency status (5% FBS), the cells were assigned into four groups: 1) G1 - 15% FBS (positive control); 2) G2 - 5% FBS (negative control); 3) G3 - 5% FBS+LPT 3 J/cm2; and 4) G4 - 5% FBS+LPT 5 J/cm2. For the LPT groups, two laser irradiations at 6 h intervals were performed using a continuous wave InGaAlP diode laser (660 nm, with a spot size of 0.028 cm2, 10 mW) in punctual and contact mode. Cell viability was assessed via an MTT reduction assay immediately after the second laser irradiation (0 h) and 24, 48, and 72 h later. We found that G3 and G4 presented a significantly higher cell growth rate when compared with G2 (p < 0.01). Moreover, G4 exhibited a similar cell growth rate as G1 throughout the entire experiment (p > 0.05). These findings indicate that LPT with 5 J/cm2 can enhance the growth of SHEDs during situations of nutritional deficiency. Therefore, LPT could be a valuable adjunct treatment in tissue engineering when using stem cells derived from the dental pulp of primary teeth.